Higher education teachers’ attitudes towards English medium instruction: A three-country comparison - Dearden, Julie; Macaro, Ernesto (Studies in second language learning and teaching, 2016)
We report on a small scale study carried out in Austria, Italy and Poland which investigated the attitudes of university teachers engaged in teaching their academic subject through the medium of English. The data consisted of 25 teacher interviews. We focused on the topics of internationalisation of universities, on policy and resourcing, and on the levels of English proficiency (theirs and those of their students) needed for effective English medium instruction (EMI). We also observed whether there were differences among the respondents from the three countries and attempted to relate any differences to the linguistic, educational and political context of each. Our findings suggest that whilst very similar concerns are in the minds of the teachers regardless of the country they were teaching in, some interesting variability in attitudes, relating to language and to history, could be detected. To our knowledge, this is the first study on EMI that compares teacher attitudes in three countries, hence its exploratory nature. Our findings would suggest that further research of such comparative kind might provide insights into how the phenomenon of EMI is being introduced and accepted across the world.